2014
DOI: 10.1080/15287394.2015.956025
|View full text |Cite
|
Sign up to set email alerts
|

A Permethrin/Allethrin Mixture Induces Genotoxicity and Cytotoxicity in Human Peripheral Blood Lymphocytes

Abstract: Two pyrethroids, permethrin and allethrin, are often combined for large-scale use in public health programs to control vector-borne diseases. In this study, the genotoxic potential of a commercial formulation of permethrin and allethrin was examined using cultured human peripheral blood lymphocytes (PBL). Genotoxicity was evaluated using the cytokinesis-block micronucleus cytome (CBMN cyt) assay by measuring the frequency of micronuclei (MN), nuclear division index (NDI), formation of nucleoplasmic bridges (NP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 31 publications
1
6
0
2
Order By: Relevance
“…On the other hand, diverse studies about genotoxic and/ or cytotoxic effects obtained with pure and commercial formulations of diverse pesticides indicate that commercial formulations may contain additional unsafe xenobiotics supporting the importance of evaluating not only the active principle but also the commercial formulation, which in fact constitutes the real hazard from agrochemicals (42)(43)(44)(45)(46)(47)(48)(49)(50)(51).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, diverse studies about genotoxic and/ or cytotoxic effects obtained with pure and commercial formulations of diverse pesticides indicate that commercial formulations may contain additional unsafe xenobiotics supporting the importance of evaluating not only the active principle but also the commercial formulation, which in fact constitutes the real hazard from agrochemicals (42)(43)(44)(45)(46)(47)(48)(49)(50)(51).…”
Section: Discussionmentioning
confidence: 99%
“…Ramos-Chávez et al (2015) realizaron exposición de células sanguíneas humanas periféricas a permetrina y aletrina, mostrando un incremento en la frecuencia de micronúcleos, porcentaje de células apoptóticas y tejido necrótico. Vences-Mejía et al (2012) evaluaron el efecto de transflutrin y D-aletrina en ratas "Wistar" expuestas a estos por inhalación (utilizando redes de mosquitero repelentes).…”
Section: Toxicología De Plaguicidas (Estudios In Vitro E In Vivo)unclassified
“…The p-pDDT and PMT were supplied at 15 or 150 µM. These concentrations were selected based on literature data of LD50 or IC50 (Willemin et al, 2015;Leibold and Schartz 1993;Zucchini Pascal et al, 2012;Ramos-Chavez et al, 2015) and rat PBPK mathematical models extracting blood and liver concentrations from in vivo assays in which rat were feed with PMT corn oil (Willemin et al, 2014). In these studies, we found values ranging between 2.5 and 125 M. Stock solutions were 50 mM in DMSO, leading to working solution with a DMSO highest concentration of 0.3%.…”
Section: Exposure To Pesticidesmentioning
confidence: 99%